2007
DOI: 10.1086/518363
|View full text |Cite
|
Sign up to set email alerts
|

Coronal Heat: Solar Loop Temperatures from TRACE Triple-Filter Data

Abstract: The Transition Region and Coronal Explorer (TRACE) has state-of-the-art spatial resolution and shows the most detailed images of coronal loops ever observed. The temperatures of these loops are primarily derived from the 171 to 195 filter ratio, with data from the third filter at 284 used by several authors to improve theÅ A precision of the derived temperatures. Most of these studies assume that the plasma is isothermal and model the loops primarily as uniform temperature structures with footpoint-dominated h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…The lofty goals mentioned above might appear to be out of reach. These results seem reminiscent of the DEM work described by Schmelz et al (2007) for TRACE. TRACE and AIA have similar spatial resolution, but TRACE has only three coronal filters.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The lofty goals mentioned above might appear to be out of reach. These results seem reminiscent of the DEM work described by Schmelz et al (2007) for TRACE. TRACE and AIA have similar spatial resolution, but TRACE has only three coronal filters.…”
Section: Discussionsupporting
confidence: 72%
“…Most of these studies assumed that the plasma was isothermal, but see Aschwanden & Nightingale (2005) for a different case. Schmelz et al (2007) found, however, that even these triple-filter data were insufficient to constrain the loop plasma temperature. They showed this explicitly by constructing DEMs with a Markov Chain Monte Carlo based reconstruction algorithm (Kashyap & Drake 1998).…”
Section: Discussionmentioning
confidence: 98%
“…In that work the temperature map was derived from the multiwavelength observations by the EIT on SOHO. However, the interpretation of EUV images in terms of temperatures is complicated and not unique (e.g., Schmelz et al 2007;Frazin et al 2005b).…”
Section: Discussionmentioning
confidence: 99%
“…The effects of plasma multithermality are discussed in Reale et al (2007) and for TRACE in e.g. Weber et al (2005) and Schmelz et al (2007b). We return to the assumption of isothermal plasma in Sect.…”
Section: Temperature Diagnostic Using Cifrmentioning
confidence: 99%